Aging and asthma - changes in CD45RA, CD29 and CD95 T cells subsets - Todo-Bom, A (2011)
BACKGROUND: Aging is associated with thymus involution leading to a reduction in naive T cells and to an accumulation of effector-memory cells. Apoptosis is a key mechanism to clear the immune system from activated and harmful cells. In asthma the stimulation of T cells by environmental antigens can decrease naive cells and sustain activated cells. The aim of this work was to evaluate the imbalance between CD45RA and CD29 cells during the aging process and their changes in elderly asthma and to evaluate how elderly and chronic diseases like asthma can affect susceptibility to apoptosis. METHODS: Elderly and young adult healthy volunteers and elderly asthmatic patients were submitted to skin prick tests, immunoglobulin determination and flow cytometry analyses of CD3, CD4, CD8, CD45RA, CD29, and CD95. RESULTS: Serum IgE was increased in allergic patients (p=0.0001). Asthmatics presented an increase in CD4 cells (p<0.05). CD45RA was significantly decreased in elderly individuals (p<0.05) and this decrease was higher in asthmatics (p<0.05). CD29 was increased in elderly healthy individuals compared to the control young group (p=0.0001). A negative correlation between CD29 and CD45RA (p<0.05) was observed. CD95 lymphocytes increased in elderly (p=0.0001) and a positive correlation between age and CD95 (p<0.05) was found. Asthmatic patients showed significant decreases in CD95 (p=0. 0001). CONCLUSIONS: Naive cells are key cells in the defence against infections and their decrease in the elderly and in asthma is a bad prognosis factor. The reduction of apoptosis markers can promote the persistence of activated cells involved in chronic conditions.